Establishing consensus of position-specific predictors for elite youth soccer in England - Roberts, S. J.; McRobert, A. P.; Lewis, C. J.; Reeves, M. J. (Science and Medicine in Football, 2019)
Purpose: To construct a valid and reliable methodology for the development of position-specific predictors deemed appropriate for talent identification purposes within elite youth soccer in England. Method: N = 10 panel experts participated in a three-step modified e-Delphi poll to generate consensus on a series of generic youth player attributes. A follow-up electronic survey completed by coaches, scouts and recruitment staff (n = 99) ranked these attributes to specific player-positions. Results: A final list of 44 player attributes found consensus using the three-step modified e-Delphi poll. Findings indicated that player-positional attributes considered most important in the youth phase are more psychological and technical than physiological or anthropometric. Despite `hidden` attributes (e.g., coachability, flair, versatility, and vision) finding consensus on the e-Delphi poll, there was no evidence to support these traits when associated with a specific playing position. Conclusion: For those practitioners responsible for talent recruitment, our findings may provide greater understanding of the multiple attributes required for some playing positions. However, further ecological research is required to assess the veracity of our claims.